2015
DOI: 10.1039/c5cc00430f
|View full text |Cite
|
Sign up to set email alerts
|

Acylative Suzuki coupling of amides: acyl-nitrogen activation via synergy of independently modifiable activating groups

Abstract: A highly efficient palladium-catalyzed acylative cross-coupling of carboxylic amides with arylboronic acids has been achieved via synergistic activation of the C(acyl)-N bond by independently modifiable activating groups. Coupling of amides features not only good functional group tolerance but also modifiable reactivities to overcome steric hindrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(116 citation statements)
references
References 38 publications
4
112
0
Order By: Relevance
“…[47][48][49] From the outset, it was clear that for the amide bond activation concept to be generally useful,m ost crucial is the identification of easily applicable, acyclict wisted amides. The classic work on twisted amides demonstratedt hat amide bond distortion could be used to separate amidicr esonance into aminoketone-like reactivity.In2015, three independent, almost simultaneous publications on the NÀCc ross-coupling were published.…”
Section: Amide Bond Distortion In Amide Nàcc Ross-couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…[47][48][49] From the outset, it was clear that for the amide bond activation concept to be generally useful,m ost crucial is the identification of easily applicable, acyclict wisted amides. The classic work on twisted amides demonstratedt hat amide bond distortion could be used to separate amidicr esonance into aminoketone-like reactivity.In2015, three independent, almost simultaneous publications on the NÀCc ross-coupling were published.…”
Section: Amide Bond Distortion In Amide Nàcc Ross-couplingmentioning
confidence: 99%
“…[47,48,[57][58][59][60][61] The amide bond distortion in N-acyl-tert-butyl-carbamates (Boc) and N-acyl-tosylamides (Ts) has been quantitatively evaluated (Scheme 13). [47,48,[57][58][59][60][61] The amide bond distortion in N-acyl-tert-butyl-carbamates (Boc) and N-acyl-tosylamides (Ts) has been quantitatively evaluated (Scheme 13).…”
Section: N-acyl-tert-butyl-carbamates (Boc) and N-acyl-tosylamides (Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Li and Zou reportedt he first palladium-catalyzed direct acylative Suzuki cross-coupling reaction of electronically activatedc arboxylic amides through synergistic activation of the C acyl ÀNb ond (Scheme 9). [39] Initial unsuccessfula ttempts at activating the amide bond were performed by employing a non-precious nickel catalyst. Then, after screening ar ange of catalysts, bases, ligands, and solvents, the authors found that a palladium catalystw as effectivef or this transformation.T hus, the reactiono fN-phenyl,N-tosyl-benzamide with various phenylboronic acids in the presence of [Pd(PCy 3 ) 2 Cl 2 ]( 5mol %) and PCy 3 (3 mol %) afforded the corresponding products in 35-98 %y ields.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%
“…These compounds serve as starting materials for synthesis of 3-arylpropanols [6], 1,3-diarylpropan-1-ones [7], quinolines [8], β-l lactams [9], 4-aryl-2-quinolinones [10] and 1-indanones [11], as well as ligands in iridium complexes [12]. Despite the wide application of these compounds only few structures have been analyzed by X-ray di raction method: the closest examples include 1,3-di-(3-phenylpropanoylamino)benzene [13], …”
Section: Discussionmentioning
confidence: 99%